Social Inclusion Issues in Contemporary Housing Estates: The Case Study of Poljane, Maribor - Dušek, Heřman; Marneffe, Karelle; Puškárová, Michelle; Sánchez Castillo, Edgardo Ernesto; Steinicke, Carolyn; Vila Vázquez, José Ignacio (Quality of Life in a Changing World: Spatial, Social and Environmental Perspectives from Maribor and Beyond, 2026)
Social exclusion in housing estates remains a pressing challenge in Europe, where concentrated poverty and marginalised groups face persistent barriers to integration. This paper examines the case of the Poljane public housing development in Maribor, Slovenia, asking whether its location within a low-density neighbourhood and the characteristics of its residents contribute to social exclusion and urban segregation. A mixed-method approach was applied, combining field observations, semi-structured interviews with stakeholders, and literature analysis. The findings highlight the deterioration of shared spaces, tensions between Roma and non-Roma residents, and the persistence of negative external perceptions, while also noting efforts at inclusion through NGO-led initiatives. Overall, the results confirm that physical decay, high density, and social fragmentation contribute to reinforcing forms of social exclusion in Poljane.